Analysis of Factors Influencing Stock Prices of Companies in the LQ45 Index: A Study Period From 2019 to 2022 - Astuti, Ayi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
The stock market plays a crucial role in the allocation of capital and the economic growth of a country, including Indonesia. This study aims to identify the factors that influence the stock prices of companies within the LQ45 Index during the 2019-2022 period. Through an empirical analysis approach, this research explores the impact of capital structure (Debt to Equity Ratio - DER), liquidity (Cash Ratio), ownership structure (Institutional and Managerial Ownership), and company size on stock prices.This study aims to analyze the factors influencing stock prices of companies listed in the LQ45 Index during the period of 2019-2022. Financial data and market information were collected to identify significant factors affecting stock prices. The study employed multiple linear regression analysis to explore the relationship between independent variables, namely capital structure (DER), liquidity (Cash ratio), ownership structure (KI and KM), and company size (SIZE), with stock prices. The results show that, in this context, Institutional Ownership (KI) has a significant positive effect on stock prices, while Company Size (SIZE) also has a significant influence. These findings indicate that these factors collectively contribute to determining stock prices. The implications of this research provide a deeper understanding of the factors influencing stock price behavior in the capital market.